Losses of electrical energy in electrical networks - G. Yu. Kiselyov; V. M. Trotsenko; E. V. Petrova; V. A. Krivolapov; S. S. Girshin; A. A. Bubenchikov; V. N. Goryunov (Омский научный вестник)
This article discusses the relevance of reducing electrical energy losses. The actual values and plans for reducing electric energy losses in PJSC «Rosseti» and the main branches of PJSC «Rosseti Siberia» are given. The existing standards of losses in electrical networks of different voltage levels are presented. Possible ways of reducing electricity losses to achieve the targets set by the «Energy Strategy of the Russian Federation for the period up to 2035» are considered.